ANALISIS GETARAN KOMPOSIT SERAT KACA-MATRIKS EPOKSI DENGAN METODE ELEMEN HINGGA - Mustafa Mustafa (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2010)
This  aim  of  the  study  was  to  analyze  the  natural  frequency  ( n )  of  fiberglass  reinforced  polymer composite beams. The study used the finite element method for numerical analysis. For the numerical analysis, the beam was divided into 5 elements. The supports used were a cantilever with the material of fiberglass reinforced polymer composite in the form of beam with length of 1 m, width of 0.03 m, and thickness of 0.02 m. Composite material consisted of two compositions, i.e : 5% fiber glass and 95% matrix epoxy; 20% fiber glass and 80 % matrix epoxy. The devices used in the study was a computer with matlab program. The results of the study for natural frequency analysis with 5% fiberglass:  nmax  = 23334 rpm,  nmin  = 2625 rpm, whereas with 20% fiberglass:  nmax = 34033 rpm,  nmin  = 3829 rpm. The value  of  natural  frequency  ( n )  obtained  20  %  fiberglass  was  greater  than  the  value  obtained  5% fiberglass.